PENGARUH ELEMEN INTERIOR COWORKING SPACE DI SURABAYA TERHADAP KENYAMANAN KERJA PENGGUNA (OBJEK STUDI : COWORKING SPACE KORIDOR) - Achmad Haris Kaffi Kurnia; Tito Haripradianto (Jurnal Mahasiswa Jurusan Arsitektur, 2020)
Many people now work as independent workers, working in a coworoking space. Coworking space in Indonesia itself is growing, one of which is in the city of Surabaya. The Koridor is the only coworking space established by the Surabaya City Government, as part of the Surabaya mayor's vision to make Surabaya a creative and technological center at the global level. Koridor coworking space still has shortcomings in the context of interior design that need to be examined regarding interior elements and their influence on coworking space users so the purpose of this study is to examine the influence of Koridor coworking space workspace elements on the user's work comfort and to find out what interior elements are the most influence on the user's work comfort. The method used in this study is a quantitative method with a descriptive approach, using questionnaires and observations for data collection methods. The analytical method is assisted with the application of SPSS Statistics. The results of the study state that based on the results of the mean score it can be concluded that the interior element that has the highest value (very comfortable) is a variable height table variable with a value of 3.81 while for the variable variable that has the lowest value (uncomfortable) is a variable parameter type of material ceiling with a value of 3.19. Based on the results of linear regression it can be concluded that the group of factors that have the greatest influence on user comfort is the color factor group, while the group of factors that provides the least influence on user comfort is the spatial dimension factor group and the color composition.